Low-Dose Corticosteroid Treatment in Children With Mycoplasma pneumoniae Pneumonia: A Retrospective Cohort Study - Zhang, Liya; Wang, Lijun; Xu, Shanshan; Li, Huajun; Chu, Caiting; Liu, Quanhua; Zhou, Jia; Zhang, Wen; Huang, Lisu (Frontiers in Pediatrics, 2020)
Background: The clinical value of corticosteroid treatment in Mycoplasma pneumoniae pneumonia (MPP) has been controversial. Our study aimed to identify the effects of low-dose corticosteroids on the recovery of children with MPP. Methods: In this retrospective cohort study, pediatric inpatients with MPP were included from the Shanghai Children’s Mycoplasma pneumoniae pneumonia cohort study between August 2014 and July 2019. The multivariable logistic regression and propensity-score matching were used to investigate the effects of low-dose corticosteroid treatment on fever duration after admission, total fever duration, length of hospital stay, C-reactive protein recovery time and imaging recovery time with the stratification of severe pneumonia, refractory pneumonia, inflammatory biomarkers, pulmonary images, and timing of corticosteroids. Results: There were 548 patients in the corticosteroid group and 337 in the no-corticosteroid group. The corticosteroid group showed severe clinical parameters such as more severe and refractory cases, higher laboratory values, more abnomal imaging manifestations. The corticosteroid group also showed longer fever duration after admission (OR=1.9 [95%CI 1.2–3.1], P=.008), longer total fever duration (OR=1.6 [95%CI 1.1–2.3], P=.011), longer hospital stay (OR=2.8 [95%CI 1.9–4.0], P<.001), and longer CRP recovery time (OR=2.1 [95%CI 1.1–3.9], P=.021) in the regression model after the adjustment for severity. Although low-dose corticosteroids were associated with shortened imaging recovery time in patients with high level laboratory values, pulmonary imaging could be completely recovered in both groups. The trend of these results was consistent even after stratiﬁcations and a propensity scores matching analysis. Conclusions: Low-dose corticosteroids may not be beneficial in children inpatients with MPP and further studies on proper treatment modality are needed in the MRMP era.